DETERMINATION OF 5H-BENZO[2,3][1,4]OXAZEPINO[5,6-B]INDOLES IN RAT PLASMA BY REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC-ULTRAVIOLET METHOD: APPLICATION TO PHARMACOKINETIC STUDIES - Singh, Ashok K; Raj, Vinit; Rai, Amit; Keshari, Amit K; Kumar, Pranesh; Saha, Sudipta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Recently, we reported newly synthesized 5H-benzo[2,3][1,4]oxazepino[5,6-b]indole) derivatives and proved their cytotoxicity against hepatocellular carcinoma specific Hep-G2 cell lines. We attempted herein to describe a reversed-phase high-performance liquid chromatographic method for the determination of three most active compounds 6a, 10a, and 15a in rat plasma to predict their pharmacokinetics parameters before in vivo study. Methods: A rapid and sensitive reversed-phase high-performance liquid chromatographic was employed for the determination of 6a, 10a, and 15a in rat plasma. Each compound was separated by a gradient elution of acetonitrile and water with 1 mL/min flow rate. The detector was set at 270, 285, and 275 nm for 6a, 10a, and 15a and the recorded elution times were 2.00, 2.87, and 1.88 min, respectively. Results: The calibration curve was linear with R2 of 0.938, 0.875, and 0.923 over the concentration range of 0.1â€“50 Î¼g/mL. The inter- and intra-day variations of the assay were lower than 12.26%; the average recovery of 6a, 10a, and 15a was 97.31, 92.56, and 95.23 % with relative standard deviation of 2.12%, 3.25%, and 2.28%, respectively. The Cmax and Tmax were 46.34, 18.56, and 25.65 Î¼g/mL and 2.0, 4.0, and 4.0 h for 6a, 10a, and 15a, respectively, which indicate a robust method of detection in the present experiment. Conclusion: The study suggests that all of the three compounds have a lower rate of absorption, higher volume of distribution, and lower clearance rate, indicating good therapeutic response for in vivo activity. Â